Das Danielbuch und die Danielfigur in jüdischer, christlicher und islamischer Tradition - Konrad Kremser (Warszawskie Studia Teologiczne)
A book and a character named „Daniel“ are known in Jewish, Christian and Islamic traditions. The book of Daniel is partly viewed as a prophetic book and Daniel accordingly as a prophet, partly it is explicitly denied that the book and the character „Daniel“ are prophetic. A comparison of the different traditions helps to identify lines of development.